The Identification of FN1 as an Early Diagnostic Marker for Recurrent Abortion by Single-Exosome Profiling - Wang C; Lu Z; She G; Chen K; Zhou H; Zhan X; Yu H; Pi L; Zuo L; Che D (International Journal of General Medicine)
Chenlu Wang,1,* Zhaojin Lu,1,* Guangpeng She,2 Kaining Chen,1 Huazhong Zhou,1 Xueli Zhan,3 Hongyan Yu,1 Lei Pi,1 Liandong Zuo,4 Di Che1 1Department of Clinical Biological Resource Bank, Guangzhou Institute of Pediatrics, Guangdong Provincial Key Laboratory of Research in Structural Birth Defect Disease, Guangzhou Women and Children’s Medical Center, Guangzhou Medical University, Guangzhou, 510620, People’s Republic of China; 2Department of Laboratory Medicine, The Second Affiliated Hospital, School of Medicine, South China University of Technology, Guangzhou, Guangdong, 510180, People’s Republic of China; 3Department of Pediatric Surgery, Guangzhou Institute of Pediatrics, Guangdong Provincial Key Laboratory of Research in Structural Birth Defect Disease, Guangzhou Women and Children’s Medical Center, Guangzhou Medical University, Guangzhou, Guangdong, 510620, People’s Republic of China; 4Department of Andrology, Guangzhou Women and Children’s Medical Center, Guangzhou Medical University, Guangzhou, 510620, People’s Republic of China*These authors contributed equally to this workCorrespondence: Di Che, Department of Clinical Biological Resource Bank, Guangzhou Institute of Pediatrics, Guangdong Provincial Key Laboratory of Research in Structural Birth Defect Disease, Guangzhou Women and Children’s Medical Center, Guangzhou Medical University, No. 9 Jinsui Road, Guangzhou, Guangdong, 510620, People’s Republic of China, Email chedi@gwcmc.org Liandong Zuo, Department of Andrology, Guangzhou Women and Children’s Medical Center, Guangzhou Medical University, 9 Jinsui Road, Guangzhou, Guangdong, 510620, People’s Republic of China, Email zuold@163.comPurpose: Recurrent abortion(RA) is a prevalent adverse pregnancy event. Exosomes, secreted by various body fluids, are known to play a role in disease diagnosis and serve as biomarkers through intercellular communication. This study aims to analyze single exosomes in patients with recurrent abortion to identify new biomarkers that may significantly contribute to recurrent abortion, providing new directions for its treatment.Patients and Methods: A total of 244 serum exosomes were collected, including 216 patients with recurrent abortion of varying outcomes and 28 normal pregnancies. We performed the proximity barcoding assay (PBA) to analyze single exosome surface proteins, which allowed us to identify individual exosomes related to the development of RA as well as the major subpopulations of exosomes. After PBA treatment, samples were analyzed for single exosomes, and exosomes from each group were compared using volcano plots, dot plots, and ROC curves.Results: By intersecting all significantly differentially expressed genes obtained from comparisons between the normal pregnancy control group and the recurrent abortion group, including the RA before abortion, RA after abortion, and RA non-pregnancy groups, we identified seven shared differential genes: FN1, APIPOQ, CDH13, DSG1, CLDN4, CD36, and ULBP3. Among these, FN1 was the most significantly differentially expressed gene in exosomes, with FN1 | log2 (fold change) |> 1.5 and an AUC of 0.7414. In addition, exosome subpopulation analyses showed that cluster 11 accounted for the largest proportion of the total 16 subpopulations, and FN1 was the marker with the highest concentration of cluster 11.Conclusion: Single-exosome profiling and exosome subpopulations of RA by PBA yielded significant differential gene FN1, which provides new possibilities for diagnostic screening of RA.Keywords: recurrent abortion, exosomes, FN1, PBA